Enhancing Reading Comprehension through Think, Pair, and Share Technique in Tenth Grade of MA Raudlatul Ulum Putra - Mahfudillah Syam, Ahmad (LPPI Universitas Al-Qolam Malang, 2022)
This study was aimed to enhance reading comprehension at the tenth grade students of MA. Raudlatul Ulum Putra in academic year 2021/2022 by using think-pair-share technique. The researcher used Classroom Action Research (CAR) as the research design. The subject under this study was 24 students of tenth grade of MA. Raudlatul Ulum Putra. There were some instruments used to support this research, such as: observation sheet, field note, lesson plan, and test. The result of this study showed that think, pair, share technique had a positive effect on the students’ reading skill. In pre-test, there are only 1 students from 24 students who got the minimum standard score, whereas the mean score was 36.14. In cycle 1, there are 2 students who got the minimum standard score, whereas the mean score was 59.9. In cycle 2, there are 3 students who did not reach the minimum standard score and 21 students could reach it, where the mean score was 79.8. Based on the result, the research improved the students’ reading comprehension at the tenth grade of MA. Raudlatul Ulum Putra successfully. Furthermore, the researcher supposed that using this technique was very useful to motivate students in reading. Key words: reading comprehension; think-pair-share technique; enhancement; education; teaching